The Effects of Psychological Factors and Financial Literacy on Financial Management - Bagaskara, Kurniarga; Baridwan, Zaki; Nurofik, Nurofik (Trunojoyo University of Madura, 2024)
The study aims to test the influence of mental accounting and financial literacy on financial management on lecturers and postgraduate students in economics and business in Yogyakarta. Financial management is one of the important aspects of everyday life that relates to the financial decisions taken by individuals. In this study, mental accounting represents psychological factors that influence financial decision-making, while financial literacy represents the knowledge needed to make the right financial decisions. Primary data was collected from 122 respondents who are lecturers and postgraduate students in economics and business in Yogyakarta. Double regression analysis is used to test the impact of mental accounting and financial literacy on financial management. Research results show that mental accounting and financial literacy have a positive and significant influence on financial management. These findings suggest that respondents in this study have applied the concept of good mental accounting by applying income allocation, perception of income source differences based on purpose use, and evaluation of money spent from various sources of income. The results also show that respondents have sufficient financial literacy to create more optimal financial management. The conclusion that can be drawn from this study is that the better the mental accounting and financial literacy of the individual, the better their financial management.